2014
DOI: 10.1007/s12010-014-1147-0
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role of the N- and C-terminals of Laccase from Pleurotus florida on the Laccase Activity and Stability

Abstract: POXA1b is the most thermostable laccase isoenzyme from Pleurotus ostreatus. POXA1b is remarkably stable at alkaline pH (the t1/2 at pH 10 was 30 days), and its C-terminal affects its catalytic and stability properties. We cloned POXA1c from P. florida, which showed 99 % identity with POXA1b. POXA1c was functionally expressed in Pichia pastoris. The functions of the N and C termini of POXA1c were investigated using site-directed mutagenesis. Compared with POXA1c, the N-terminal R5V site effectively increased th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…51 Although the above laccases hold elongated C-terminal tails that lie closer to the entrance of TNC than in our case, mutations added to PK2 C-terminal tail make it more flexible and may entail a displacement that could improve the access to the TNC channel. 52,53 This hypothesis will be verify when the RY2 variant is crystallized, taking advantage of the high production yields obtained in yeast.…”
Section: Enzyme Stabilitymentioning
confidence: 92%
“…51 Although the above laccases hold elongated C-terminal tails that lie closer to the entrance of TNC than in our case, mutations added to PK2 C-terminal tail make it more flexible and may entail a displacement that could improve the access to the TNC channel. 52,53 This hypothesis will be verify when the RY2 variant is crystallized, taking advantage of the high production yields obtained in yeast.…”
Section: Enzyme Stabilitymentioning
confidence: 92%
“…Structures of some fungal laccase isozymes exhibit an extended C‐terminal, which may block this channel, significantly impairing the catalytic efficiency of the enzyme . A recent study by Hu and coworkers showed that the activity of a laccase from the fungus Pleurotus florida could be increased substantially when its C‐terminal was truncated by 13 residues . Substrate accessibility to the active site also affects catalytic efficiency of the enzyme.…”
Section: Laccasesmentioning
confidence: 99%
“…At room temperature, a certain molar concentration of laccase was added in buffers with different pH (pH 2.0-6.0, 0.1 mol/l HAc-NaAc) to measure the optimum pH for enzyme activity [9].…”
Section: Optimum Phmentioning
confidence: 99%